Building Research Station Golden Jubilee Congress : Proceedings - Building Research Station Golden Jubilee Congress (1971 : Building Research Station, Garston, England); Lea, F. M. (Frederick Measham), 1900- (London : Her Majesty's Stationery Office, 1972)
03